Phytotoxicity and uptake of roxarsone by wheat (Triticum aestivum L.) seedlings. (December 2016) - Fu, Qing-Long; Blaney, Lee; Zhou, Dong-Mei
Abstract: Roxarsone (ROX), the primary aromatic arsenical additive (AAA) used in animal feeding operations, is of increasing concern to environmental and human health due to land application of ROX-laden animal manure. Few studies have investigated the phytotoxicity, uptake mechanisms, and speciation of AAA in crop plants. In this study, wheat seedlings were employed to address these issues under hydroponic conditions. Compared to inorganic arsenic, ROX was less toxic to wheat root elongation. Wheat roots were more sensitive to ROX stress than shoots. For the first time, metabolized inorganic arsenic was detected in plants, although ROX was the predominant detected arsenic species in wheat seedlings. ROX uptake and toxicity to roots were inhibited by humic acid at concentrations higher than 50 mg/L due to interaction with ROX. Phosphate enhanced ROX uptake, but no trends were observed for ROX uptake in the presence of glycerol at concentrations lower than 250 mM. In addition, ROX uptake was significantly decreased by silicate (Si(IV), 0.5–10 mM) and the metabolic inhibitor, 2, 4-dinitrophenol (0.5–2 mM), indicating that ROX transport into wheat roots was actively mediated by Si(IV)-sensitive transporters. These findings provide important insights into the fate and speciation of AAA in soil-water-plant systems relevant to human health. Graphical abstract: Highlights: ROX is less toxic to wheat seedlings than As(III) and As(V). Compared to As(V) and As(III), ROX is less accumulated into wheat shoots. In wheat plants, ROX was poorly metabolized into inorganic As. The uptake and toxicity of ROX to wheat roots was inhibited by humic acid. A transporter-mediated active process is responsible for ROX transport into roots. Abstract : ROX was less toxic to wheat roots than inorganic As and was actively transported into wheat roots via Si(IV)-sensitive transporters with minor amounts of metabolized As(III) and As(V).